Pengaruh Lingkungan Kerja Non Fisik terhadap Kinerja Karyawan: Studi Kasus pada PT. Kimia Farma Apotek Palembang - Alhari Ramadana, Muhammad; Andriana, Isni; Farla, Wita (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
The purpose of this study was to determine the effect of non-physical work environment on employees of PT. Kimia Farma Apotek Palembang. The population in this study were 74 respondents, all employees of PT. Kimia Farma Apotek Palembang. The sampling technique used a saturated sampling technique (census) with questionnaires distributed to all employees of PT. Kimia Farma Apotek Palembang and the data analysis technique used was simple linear regression analysis. The results of this study indicate that there is a positive and significant influence between non-physical work environment on employee performance